Incidencia de la temperatura y humedad en pollos de engorde Cobb 500 y su efecto en enfermedades respiratorias en la avícola Freire de la ciudad de Milagro - Saquinga Solorzano, Ericka Nicole (2023)
The experimental work was carried out in the "Freire" poultry farm in the city of Miracle, province of Las Guayas between the months of February - March 2023. The objective of this study is to identify the highest temperature and humidity that occurs in the poultry house. Freire and determine the presence of diseases in which an evaluation of mortality was carried out in which 200 chickens of the Cobb 500 line divided between males and females were used. Likewise, the temperature and relative humidity were evaluated within which in the week (1-2) gave us 29°C as a result, likewise in week 3, which was 27°c and the week (4,5,6) gave us 28°C as a result in terms of temperature levels throughout throughout the 6 weeks of study. As for the humidity, a follow-up was carried out, resulting in week 1, it gave us 67 as a result, likewise in week 2 and 3, which was 66 and week (3,4,5,6) gave us as a result a 68 in terms of humidity as a descriptive research method, the description of the events within the poultry farm throughout the project was helped, likewise the deductive method was obtained that helped the analysis of the conceptual variables. As for the method used, it was the experimental statistical method in which it was descriptive, based on describing the events within the poultry industry and deductive to analyze the conceptual causes, likewise, mean, median and mode were obtained. Respiratory diseases were also found that affected the development of life in birds such as infectious bronchitis is caused by nasal congestion and fever, which can cause a slow death. Finally, the mortality variable was analyzed, which gave us 19.5% as a result, which indicates the percentage of losses that was obtained in the February-March period, which thus presented economic losses.